LINGUOCOGNITIVE ANALYSIS OF “PARENTS” CONCEPT IN ENGLISH AND UZBEK LANGUAGES - Khayitova Shohida Erkin Qizi, (Лучшие интеллектуальные исследования, 2024)
This article is written about the concept of “Parents” in English and Uzbek languages from linguistic-cognitive approach. In this article conclusions of proverbs with the concept of “parents” and the place and importance of proverbs in human life are mentioned. In different languages when we compare proverbs and study the differences and similarities between them we found out.